Removal of Some Surfactants from Dilute Aqueous Solutions Using Charcoal - Mahmoud M. Saleh; Asem A. Atia (Adsorption Science & Technology)
The efficiency of charcoal in removing anionic, cationic and non-ionic surfactants from their aqueous solutions was studied. Measurements were performed on Triton (TX-100), cetylpyridinium chloride (CPC) and dodecylbenzene sulphonate (DBS) as examples of non-ionic, cationic and anionic surfactants, respectively. Removal efficiencies of up to 90% were achieved for all the surfactants studied. In addition, synergistic interaction between the non-ionic and either cationic or anionic surfactants was demonstrated. The extent of adsorption of non-ionic surfactants was improved by the addition of either the anionic or cationic surfactants. Complete adsorption isotherms were obtained for the three surfactants at 28°C. The lateral interaction coefficient and the standard free energy of adsorption were calculated from an analysis of the adsorption data according to the modified Frumkin isotherm.